Construction of CoP/NiCoP Nanotadpoles Heterojunction Interface for Wide pH Hydrogen Evolution Electrocatalysis and Supercapacitor. Issue 36 (20th August 2019) - Lin, Yan; Sun, Kaian; Liu, Shoujie; Chen, Xiaomeng; Cheng, Yuansheng; Cheong, Weng‐Chon; Chen, Zheng; Zheng, Lirong; Zhang, Jun; Li, Xiyou; Pan, Yuan; Chen, Chen
Abstract: Constructing well defined nanostructures is promising but still challenging for high‐efficiency catalysts for hydrogen evolution reaction (HER) and energy storage. Herein, utilizing the differences in surface energies between (111) facets of CoP and NiCoP, a novel CoP/NiCoP heterojunction is designed and synthesized with a nanotadpoles (NTs)‐like morphology via a solid‐state phase transformation strategy. By effective interface construction, the disorder in terms of electronic structure and coordination environment at the interface in CoP/NiCoP NTs is created, which leads to dramatically elevated HER performance within a wide pH range. Theoretical calculations prove that an optimized proton chemisorption and H2 O dissociation are achieved by an optimized phosphide polymorph at the interface, accelerating the HER reaction. The CoP/NiCoP NTs are also proved to be excellent candidates for use in supercapacitors (SCs) with a high specific capacitance (1106.2 F g −1 at 1 A g −1 ) and good cycling stability (nearly 100% initial capacity retention after 1000 cycles). An asymmetric supercapacitor shows a high energy density (145 F g −1 at 1 A g −1 ) and good cycling stability (capacitance retention is 95% after 3200 cycles). This work provides new insights into the catalyst design for electrocatalytic and energy storage applications. Abstract : A CoP/NiCoP heterojunction with the unique morphology like nanotadpoles (NTs) is designed and synthesized utilizing the differences in surface energies of the (111) crystal planes between CoP and NiCoP. By effective interface constructing, the CoP/NiCoP NTs exhibit superior electrocatalytic performance for hydrogen evolution within a wide pH range.